Factors that Correlate with The Health Services Seeking on Breast Cancer Patients - Dini Fathania; Laili Rahayuwati; Desy Indra Yani (Jurnal Keperawatan Padjadjaran, 2019)
Most cases of breast cancer are found to be in an advanced stage. This is because of the patient delay in coming to health service after the emergence of early symptoms of breast cancer. It is necessary to identify factors that allegedly prevent patients from seeking health services as early as possible. The purpose of this study was to analyze factors related to the search for health services. This research used cross-sectional method. The population of this study was breast cancer patients where the sampling technique using consecutive sampling with the number of samples researched as many as 100 people. Data were obtained through a reliable questionnaire to use (Alpha Cronbach’s questionnaire = 0.92, Alpha Cronbach’s health questionnaire = 0.85). Analysis of this research data using univariate (frequency distribution), bivariate (Chi-Square) and multivariate (logistic regression).The result of bivariate analysis showed that the variables related to health seeking behavior are education (ρ value = 0.02; r = 0.3) and health belief (ρ value = 0.01; r = 0.24). While the variables that most related to health service seeking behavior was health belief (ρ value = 0.02) and OR value 3.46. This could be caused by patient’s health belief in which the patient assumes that the symptoms were not dangerous and the choice of alternative medicine as the first choice and the patient’s fear of treatment due to lack of information that obtained by the patient. It can be concluded that health beliefs are the most correlated factor with health-seeking behavior so it is necessary to consider the prevention efforts of breast cancer especially related to health belief. Community beliefs about routine health checks should be key interventions such as counseling and discussions with the community regarding the importance of routine health screening as part of early detection of disease.